REINFORCEMENT DALAM KONSELING KELOMPOK DAN KONSENTRASI BELAJAR SISWA - Wardani, Fitria Esti; Purwati, Purwati; Sugiyadi, Sugiyadi (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2015)
This study aimed to determine the effect of group counseling with reinforcement techniques to increased concentrations of student learning. The study was conducted on students of class VIII B of SMP Negeri 10 Magelang City. Subjects selected by purposive sampling. This study uses a study design one group pre test-post test design. Samples taken as many as 10 students with the treatment given in the form of group counseling through reinforcement techniques. Methods of data collection is done by using a questionnaire study and documentation. The data was analyzed using non-parametric statistical method of SPSS version 16.0 for Windows using the Wilcoxon test match pairs test. The results showed that group counseling with reinforcement techniques affect positively towards increased concentration of student learning. This is evidenced by the increase in average by 13% after a given group counseling with reinforcement techniques. In addition, increase the concentration of studentlearning is characterized by the different aspects and indicators of learning concentration. One of them is a student who initially lacked concentration in following the lessons, now being able concentration in the course.